Kraftflussgerechte Fused Layer Modeling-Strukturen mit kurzfaserverstärktem Filament - Völkl, Harald; Steck, Patrick; Franz, Michael; Wartzack, Sandro (Konstruktion, 2020)
Additive manufacturing processes such as Fused Layer Modeling (FLM) offer a high degree of design freedom exploited by Design for Additive Manufacturing (DfAM). The present paper proposes a systematic approach for design and simulation of load path optimised FLM structures, comprising four steps: 1. Topology optimisation with orthotro-pic material model generates a load-path-optimised structure and provides optimised material orientations. 2 . The obtained optimisation results are converted into extrusion paths for FLM printers. 3. Printer specific building source is generated. 4. A structural mechanics FE simulation allows to determine the lightweight potential exploited.
CRIS-Team Scopus Importer:2021-04-19